Why are concavity conditions not satisfied in the cost function? The case of Japanese manufacturing firms during the bubble period - Kazuo Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2008)
This paper examines empirically some of the reasons why Japanese manufacturing firms frequently fail to satisfy concavity conditions of the cost function. We focus on the 'bubble period' in the 1980s when land was in great demand for reasons related to both production and speculation, and land prices soared. By estimating the translog cost function with land as one of production inputs for manufacturing firms, we find that violation of concavity resulted from borrowing constraints and large adjustments of employment. We also demonstrate that elasticities of substitution between land and other inputs and input demand with respect to land rental prices are both estimated with large biases if the firms violating concavity are not excluded from the analysis.
Keywords: D24; R14; 330; Land; Translog cost function; Concavity; Industrie; Betriebswirtschaftliche Produktionsfunktion; Kostenfunktion; Spekulationsblase; Bodenpreis; Japan